Low-intensity electromagnetic field as a new engineering oriented bioaugmentation strategy for anammox granules - Wang, Zhibin; Liu, Pengpeng; Zhou, Jing; Ismail, Sherif; Ahmad, Shakeel; Awad, Hanem M.; Ni, Shou-Qing (Frontiers in Environmental Science, 2022)
Improving the relative abundance of bacteria and their activity is still the basis for the efficient operation of anammox process. Here, biomagnetic effect was used to promote mature anammox granules. Batch test results show that the application of an electromagnetic field (EMF) with a strength of 0.09 μT increased the nitrogen removal performance of anammox by 32.44% while higher strength EMF of 0.20 and 0.25 μT inhibited the activity of anammox bacteria. Long-term experiment indicated that the addition of EMF with a strength of 0.09 μT greatly improved nitrogen removal performance of the mature granular sludge, especially the total nitrogen removal performance increased by 15.3%. After 120 days of reactor operation, the nitrogen loading rate was increased to 6.4 kg N/m3/d, and the total nitrogen removal rate of the reactors with and without EMF addition reached 4.92 kg N/m3/d and 4.25 kg N/m3/d, respectively. Throughout the experiment, the removal rate of ammonia and nitrite of anammox reactor with 0.09 μT EMT addition was always higher than that without EMF addition. The high-throughput sequencing analysis showed that the proportion of Candidatus Brocadia in reactors with and without EMF addition were 21.3% and 15.8%, respectively. The application of EMF with an intensity of 0.09 μT increased the relative abundance of the main anammox bacteria. 70 kos were enriched under EMF conditions, including ko00780 (Biotin metabolism), ko00540 (Lipopolysaccharide biosynthesis), ko00590 (Arachidonic acid metabolism). 51 kos like ko03030 (DNA replication) decreased after EMF addition. This study demonstrates the feasibility of EMF to promote anammox and expands the application of EMF in wastewater treatment.